2017
DOI: 10.1177/0278364917709942
|View full text |Cite
|
Sign up to set email alerts
|

Model based estimation of ellipsoidal object using artificial electric sense

Abstract: In this article we address the issue of shape estimation using electric sense inspired by the active electric fish. These fish can perceive their environment by measuring the perturbations in a self-generated electric field caused by nearby objects. The approach proceeded in three stages. Firstly the object was detected and its electric properties (insulator or conductor) identified. Secondly, the object was localized using the MUSIC (MUltiple SIgnal Classification) algorithm, which was originally developed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…In a second phase, some maps built beforehand in simulation are used to determine the ellipsoid aspect ratio and the object's lateral distance and size using an equivalent sphere model and a Gaussian process regression. The second contribution was proposed by Lanneau et al [13]. Similarly, the location and size estimation of ellipsoidal objects were separated and solved in cascade.…”
Section: Previous Work On Electric Sensementioning
confidence: 99%
See 3 more Smart Citations
“…In a second phase, some maps built beforehand in simulation are used to determine the ellipsoid aspect ratio and the object's lateral distance and size using an equivalent sphere model and a Gaussian process regression. The second contribution was proposed by Lanneau et al [13]. Similarly, the location and size estimation of ellipsoidal objects were separated and solved in cascade.…”
Section: Previous Work On Electric Sensementioning
confidence: 99%
“…However, our experiments have shown that the model remains reliable for an object whose size is below 1/4 of the robot length (5cm). Finally, in our experiments, we consider that the orientation θ of the object ranges in [0, π] and the object conductivity γ o is either equal to 1e 5 for conductive objects, or 1e −5 for insulating ones [13]. The parameter space being bounded, when a perturbation on the electric measurements is detected, our method consists in discretizing the object parameters interval, to create a base of candidate solutions, and to test each of them to find the best fitting between estimations and measurements (the lower g).…”
Section: A Model-based Heuristic a Overview Of The Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…In (Servagent et al 2013), the current measurement mode has been implemented through a family of sensors consisting of some plastic slender probes on which are arranged a few metal electrodes in different configurations (see one of them in figure 1-b). In recent years, all these sensor technologies were used to address different issues in underwater robotics ranging from model-based localization (Solberg et al 2008, to reactive navigation (Boyer et al 2013), underwater docking (Boyer et al 2015), and shape recognition (Bai et al 2015, Lanneau et al 2017. Recently, the electric sense has been proposed as an assistance for visual feedback in virtual reality (Fang et al 2016).…”
Section: Introductionmentioning
confidence: 99%